Influence of MRI Examinations on Animal Welfare and Study Results. Issue 8 (August 2020) - Baier, Jasmin; Rix, Anne; Drude, Natascha Ingrid; Darguzyte, Milita; Baues, Maike; May, Jan-Niklas; Schipper, Sandra; Möckel, Diana; Palme, Rupert; Tolba, René; Kiessling, Fabian
Abstract : Objectives: Magnetic resonance imaging (MRI) is considered to be well tolerated by laboratory animals. However, no systematic study has been performed yet, proving this assumption. Therefore, the aim of this study was to investigate the possible effects of longitudinal native and contrast-enhanced (CE) 1-T and 7-T MRI examinations on mouse welfare as well as 4T1 breast cancers progression and therapy response. Material and Methods: Forty-seven healthy and 72 breast cancer-bearing mice (4T1) were investigated. One-Tesla (ICON) and 7-T (Biospec) MRI measurements were performed thrice per week under isoflurane anesthesia in healthy BALB/c mice for 4 weeks and 3 times within 2 weeks in tumor-bearing animals. Animal welfare was examined by an observational score sheet, rotarod performance, heart rate measurements, and assessment of fecal corticosterone metabolites. Furthermore, we investigated whether CE-MRI influences the study outcome. Therefore, hemograms and organ weights were obtained, and 4T1 tumor growth, perfusion, immune cell infiltration, as well as response to the multikinase inhibitor regorafenib were investigated. Statistical comparisons between groups were performed using analysis of variance and Tukey or Bonferroni post hoc tests. Results: Mice showed no alterations in the observational score sheet rating, rotarod performance, heart rate, and fecal corticosterone metabolites ( P > 0.05) after repeated MRI at both field strengths. However, spleen weights were reduced in all healthy mouse groups that received isoflurane anesthesia ( P < 0.001) including the groups investigated by 1-T and 7-T MRI ( P = 0.02). Neither tumor progression nor response to the regorafenib treatment was affected by isoflurane anesthesia or CE-MRI monitoring. Furthermore, immunohistological tumor analysis did not indicate an effect of isoflurane and MRI on macrophage infiltration of tumors, perfusion of tumor vessels, and apoptotic cell rate ( P > 0.05). Conclusions: Repeated MRI did not influence the welfare of mice and did not affect tumor growth and therapy response of 4T1 tumors. However, systemic immunological effects of isoflurane anesthesia need to be considered to prevent potential bias. Abstract : Supplemental digital content is available in the text.